YES! Program: Adolescent Lessons Learned during a Virtual Sexual Health Program - Yvonne Allsop; Shantanu Tilak (Sexes, 2023)
Effective sexual health education provides individuals medically accurate knowledge and promotes the skills necessary for positive behaviors related to sexual health. This qualitative study employs focus groups to examine learning experiences of nine participating adolescents from a comprehensive youth empowerment and sexual health virtual summer program (The YES! Program). Focus group interviews were coded using inductive analysis to compute student learning themes (safety and prevention, preparation, and communication) and utterance coverage. Narrative inquiry highlighted the experiences of the participants. The results highlight students’ learning experiences through participation in the YES! Program and the skill outcomes of comprehensive sexual health education.